Multicore development environment for embedded processor in arduino IDE - Stefanus Kurniawan; Dareen K. Halim; Dicky H.; Tang C. M. (Universitas Ahmad Dahlan, 2020)
Internet of things (IoT) technology has found more applications that require complex computation while still preserving power. Embedded processors as the core of the IoT system approaches the need for computation by employing a parallel processor system, namely MPSoC. While various MPSoCs hardware is widely available, there is limited software support form of user-friendly libraries and development platform. There is a need for such a platform to facilitate both the study and development of parallel embedded software. arduino as the widely used embedded development platform is yet to officially support multicore programming. This work proposes an arduino-based development environment that supports multicore programming while maintaining arduino’s simple program structure, targeted at specific low-power MPSoC, the RUMPS401. The environment is fully functional, and while it targets only specific MPSoC, the proposed environment can easily be adopted to other MPSoCs with similar structures with minimal modification.